Renal Aplasia in Humans Is Associated with RET Mutations - Skinner, Michael A.; Safford, Shawn D.; Reeves, Justin G.; Jackson, Margaret E.; Freemerman, Alex J. (American journal of human genetics, 2008)
In animal models, kidney formation is known to be controlled by the proteins RET, GDNF, and GFRA1; however, no human studies to date have shown an association between abnormal kidney development and mutation of these genes. We hypothesized that stillborn fetuses with congenital renal agenesis or severe dysplasia would possess mutations in RET, GDNF, or GFRA1. We assayed for mutations in these genes in 33 stillborn fetuses that had bilateral or unilateral renal agenesis (29 subjects) or severe congenital renal dysplasia (4 subjects). Mutations in RET were found in 7 of 19 fetuses with bilateral renal agenesis (37%) and 2 of 10 fetuses (20%) with unilateral agenesis. In two fetuses, there were two different RET mutations found, and a total of ten different sequence variations were identified. We also investigated whether these mutations affected RET activation; in each case, RET phosphorylation was either absent or constitutively activated. A GNDF mutation was identified in only one fetus with unilateral agenesis; this subject also had two RET mutations. No GFRA1 mutations were seen in any fetuses. These data suggest that in humans, mutations in RET and GDNF may contribute significantly to abnormal kidney development.